The non-nutritive sweetener rebaudioside a enhances phage infectivity - Luigi Marongiu; Ewa Brzozowska; Jan Brykała; Markus Burkard; Herbert Schmidt; Bożena Szermer-Olearnik; Sascha Venturelli (Scientific Reports)
Abstract Non-nutritive sweeteners (NNS) are widely employed in foodstuffs. However, it has become increasingly evident that their consumption is associated with bacterial dysbiosis, which, in turn, is linked to several health conditions, including a higher risk of type 2 diabetes and cancer. Among the NNS, stevia, whose main component is rebaudioside A (rebA), is gaining popularity in the organic food market segment. While the effect of NNS on bacteria has been established, the impact of these sweeteners on bacterial viruses (phages) has been neglected, even though phages are crucial elements in maintaining microbial eubiosis. The present study sought to provide a proof-of-concept of the impact of NNS on phage infectivity by assessing the binding of rebA to phage proteins involved in the infection process of enteropathogenic bacteria, namely the fiber protein gp17 of Yersinia enterocolitica phage φYeO3-12 and the tubular baseplate protein gp31 of Klebsiella pneumoniae phage 32. We employed docking analysis and a panel of in vitro confirmatory tests (microscale thermophoresis, RedStarch™ depolymerization, adsorption, and lysis rates). Docking analysis indicated that NNS can bind to both fiber and baseplate proteins. Confirmatory assays demonstrated that rebA can bind gp31 and that such binding increased the protein’s enzymatic activity. Moreover, the binding of rebA to gp17 resulted in a decrease in the adsorption rate of the recombinant protein to its host but increased the Yersinia bacteriolysis caused by the whole phage compared to unexposed controls. These results support the hypothesis that NNS can impair phage infectivity, albeit the resulting effect on the microbiome remains to be elucidated.